وثوقية الأمواج فوق الصوتية في تقدير عمر الحمل قبيل الولادة باستخدام(BPD, FL) - أيوب, جهاد; الدالي, عصام; الحساب, وداد سيف الدين (Latakia University Journal -Medical Sciences Series, 2014)
-أجريت هذه الدراسة في مشفى الأسد الجامعي في اللاذقية عام 2012م وهي دراسة مستقبلية للمريضات الحوامل المراجعات لقسم التوليد وأمراض النساء خلال الفترة بين 1\9\2012و 1\9\2013م ،مع دورات طمثية معلومة و منتظمة، وذلك بعمر 37أسبوعا" حمليا" أو أكثر، شريطة عدم وجود أمراض عند الأم أو الجنين تؤثر على نمو الجنين. -شملت الدراسة 122مريضة بغض النظر عن طريقة الولادة، تم توثيق المعلومات الخاصة بكل مريضة: عمر :القطر بين BPD طول الفخذ ،:FL) وعمر الحمل المقدر بالإيكو حسب LMPالحمل حسب آخر دورة طمثية الجداريين ) خلال 24ساعة من الولادة، المجيء وكمية السائل حسب الإيكو. - تراوح عمر الحمل بين 37 و41.5 أسبوعا" بمتوسط قدره 38.6 أسبوعا"، وانحراف معياري قدره 1.1 أسبوعا " .BPD و FL، و حصلنا على قيم متقاربة تقريبا" بالاعتماد على كل من LMPحسب .BPD,LMP منه بين FL,LMP-تبين وجود ارتباط أقوى بين أعمار الحمل المقدرة ب BPD، وFL- لوحظ وجود ارتباط قوي (قيم معاملات الارتباط أعلى) بين أعمار الحمل المقدرة باستخدام كل من عندما كان المجيء مقعديا" منه عندما كان رأسيا". LMP و تلك المقدرة باستخدام كما لوحظ أن وجود كمية جيدة من السائل تعتبر ضرورية لتقدير عمر الحمل بالأمواج فوق الصوتية. This study was conducted at AL Assad University Hospital in Latakia in 2012. It was a prospective study of pregnant patients admitted Department of Obstetrics and Gynecology during the period between 1\9\2012 and 1\9\2013. These patients had regular menstrual information and were in 37th week or more of gestation and did not have any disease in the mother or fetus affecting the growth of the fetus. The study included 122 patients regardless of the mode of delivery. Each patient's information was documented: estimated gestational age by LMP (last menstrual period) and estimated gestational age by ECHO using (BPD : biparietal diameter, FL: femur length) during the 24-hour from delivery, presentation and amount of liquid by ECHO. Gestational age ranged between 37 and 41.5 weeks "with an average of 38.6 weeks" and a standard deviation of 1.1 weeks" by LMP. Results showed almost convergent values based on all BPD and FL. There was also a stronger correlation between the ages of pregnancy estimated FL, LMP than BPD, LMP. Moreover, there was presence of a strong correlation between the ages of pregnancy estimated using BPD, FL and LMP when the presentation was breech. It was also observed that the presence of a good amount of liquid is necessary to estimate the age pregnancy ultrasound.